The Effect of Process-Oriented Guided Inquiry Learning Strategy on Students' Understanding of Stoichiometry Concepts and Collaboration Skills - Ahmad, Fandi; Indah Sari, Nur (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
This study addresses low student understanding of stoichiometry and collaboration skills in vocational pharmacy education by examining the effect of Process Oriented Guided Inquiry Learning (POGIL) on these competencies among Diploma (D3) pharmacy students. An experimental method with a pretest-posttest control group design was employed. The results show that POGIL led to a significant increase in students' understanding of stoichiometry, with the experimental group achieving higher average posttest scores (a mean difference of X points) and a greater N-Gain than the control group. Additionally, students’ collaboration skills in the POGIL group improved significantly, as evidenced by a higher mean collaboration score, though this group also displayed a slightly wider range of scores.POGIL is an effective active learning strategy for improving conceptual understanding and collaboration skills in vocational pharmacy education. Its use is recommended in this context. Further research should assess its impact on other chemistry topics and on graduates’ work-readiness over time.